Dietary saponins of sea cucumber alleviate orotic acid-induced fatty liver in rats via PPARα and SREBP-1c signaling - Nagao Koji; Li Zhao-Jie; Xue Yong; Wang Jing-Feng; Wang Yu-Ming; Hu Xiao-Qian; Yanagita Teruyoshi; Xue Chang-Hu (Lipids in Health and Disease, 2010)
Abstract Background Nonalcoholic fatty liver disease is the most common chronic liver disease in the world, and is becoming increasingly prevalent. Saponins of sea cucumber (SSC) are proven to exhibit various biological activities. Therefore, the present study was undertaken to examine the effect of saponins extracted from sea cucumber (Pearsonothuria graeffei) on the preventive activity of fatty liver in rats. Methods Male Wistar rats were randomly divided into five groups, including normal control group, fatty liver model group, SSC-treated group with SSC at levels of 0.01%, 0.03% and 0.05%. Model rats were established by administration with 1% orotic acid (OA). After the experiment period, serum total cholesterol (TC), triglyceride (TG), and hepatic lipid concentrations were determined. To search for a possible mechanism, we examined the changes of key enzymes and transcriptional factors involved in hepatic lipids biosynthesis, fatty acid β-oxidation. Results Both 0.03% and 0.05% SSC treatment alleviated hepatic steatosis and reduced serum TG and TC concentration significantly in OA fed rats. Hepatic lipogenic enzymes, such as fatty acid synthase (FAS), malic enzyme (ME), and glucose-6-phosphate dehydrogenase (G6PDH) activities were inhibited by SSC treatment. SSC also decreased the gene expression of FAS, ME, G6PDH and sterol-regulatory element binding protein (SREBP-1c). Otherwise, the rats feeding with SSC showed increased carnitine palmitoyl transferase (CPT) activity in the liver. Hepatic peroxisome proliferator-activated receptor (PPARα), together with its target gene CPT and acyl-CoA oxidase (ACO) mRNA expression were also upregulated by SSC. Conclusions According to our study, the lipids-lowering effect of dietary SSC may be partly associated with the enhancement of β-oxidation via PPARα activation. In addition, the inhibited SREBP-1c- mediated lipogenesis caused by SSC may also contribute to alleviating fatty liver.